Occurrence and reasons for the suspension of elective surgery in a referral hospital - Sâmia Tavares Rangel; Júlia Larissa de Souza Silva; Rita de Cássia Lira da Silva; Ana Carolina Bezerra de Lima; Bruno Albuquerque Campos; Emanuela Batista Ferreira e Pereira (Revista Enfermagem Digital Cuidado e Promoção da Saúde, 2019)
Objective: to identify the suspension rate of elective surgeries by surgical specialties, as well as to verify the main reasons for suspension Methods: this is a quantitative study, performed at the Surgical Center of a Public Hospital. Results: from January 2013 to December 2015, 47% of the total scheduled surgeries were canceled. Regarding the reasons for suspensions, those related to human resources and the patient stood out. The specialties with the highest suspension rate were Neurosurgery, Traumatology, Vascular and General. Conclusion: the findings of the study provide subsidies for professionals and managers on a daily lived reality, since it is relevant to build indicators for health service performance evaluation